From indecent work to sustainable livelihoods in the age of the Anthropocene - Hopner V (SAGE Publications, 2023)
Humanity teeters on a critical precipice for future survival. Human activities especially our proliferating consumption levels are destroying our planet and increasing the misery of precarity, inequality, and exploitation of millions of people worldwide. Forced labour, modern slavery, and human trafficking are at least indecent and at worst obscene work, which takes place in fragile ecosystems facing irreversible devastation. The Sustainable Development Agenda 2030, and its 17 Sustainable Development Goals offer a pathway for human beings to enable decent work harmonious with environmental protections – sustainable livelihoods. Sustainable business models that are embodied in organisational values, codes of conduct, and daily practice are quintessential to ensuring both people, and the planet thrives and prosper. Industrial/organisational psychologists and vocational practitioners are key actors in ensuring sustainable livelihoods as a human right, and the basic norm in the world of work.
Keywords: Modern slavery; sustainable livelihoods; decent work; climate change; global factory